The Effect of Bottom-Up Approach in Development Planning on Regional Economic Development in North Sumatra Province, Indonesia - Panjaitan, Dikky Anugerah; Lubis, Satia Negara; Sabrina, T.; ., Badaruddin (Journal of Ecohumanism, 2024)
Development planning is a continuous process, including the discretion of decision-makers based on resource availability managed systematically. The combination of bottom-up approach and this process is becoming mainstream in Indonesia to promote the achievement of outcomes. Therefore, this research aims to determine the influence of development planning with bottom-up approach on economic development in North Sumatra region. The data analysis used is multiple linear regression with a backward approach to identify factors, influencing regional economic development. A total of 6 endogenous variables are used for aspects of regional economic development and the implementation of the approach. The results show that there are only four exogenous variables with significant influence on regional economic development, namely Village Development Planning Conference (Musrenbang), Regency/City Musrenbang, Provincial Musrenbang, and Community Aspiration Channel. These four forms of bottom-up approach should be intensified to increase the effectiveness of regional development. Meanwhile, additional variables necessitate thorough evaluation and integration into the model to enhance effectiveness and make substantive contributions to regional economic development.